Quantitative evaluation method of visual display resolution based on human visual perception. Issue 11 (18th October 2018) - Choi, Kyuha; Min, Byungseok
Abstract: As a manner of evaluating visual display resolution, contrast modulation has been widely used for decades. But, as various types of sub‐pixel layout are adopted for flat panel displays, the contrast modulation metric shows a limitation that it is not consistent with human visual perception on those displays. To overcome this limitation, a new quantitative metric is proposed in this paper by introducing structure comparison and combining it with contrast modulation. Experimental results performed on TV displays with various sub‐pixel structures demonstrate that the proposed metric has higher correlation with perceived visual resolution than the conventional metric. Abstract : As a manner of evaluating visual display resolution, contrast modulation has been widely used for decades. But, as various sub‐pixel layouts are adopted for flat panel displays, the contrast modulation metric on those displays shows inconsistency with human visual perception. To overcome this limitation, a new quantitative metric is proposed by introducing structure comparison and combining it with contrast modulation.